Effects of Vitamin D3 on asymmetric- and symmetric dimethylarginine in arterial hypertension. Issue 175 (January 2018) - Grübler, M.R.; Gaksch, M.; Kienreich, K.; Verheyen, N.D.; Schmid, J.; Müllner, C.; Richtig, G.; Scharnagl, H.; Trummer, C.; Schwetz, V.; Meinitzer, A.; Pieske, B.; et al.
Highlights: Vitamin D is suggested to be a protective factor for CV-diseases. The potential mechanism might be based on endothelial function. We conducted a double-blind randomized controlled trial. We supplemented either 2800 IU vitamin d3/day for 8 weeks or placebo. We included 200 patients with hypertension and vitamin D insufficiency. There was no sign. effect of vitamin d3 on ADMA/SDMA concentrations. There was a sign. increase of the arginine/ADMA ratio in patients 25(OH)D concentrations ≤20 ng/mL. Abstract: Background and aims: Accumulating evidence has proposed a correlation between vitamin D (25(OH)D) insufficiency and cardiovascular (CV) disease. Vitamin D associated effects on endothelial function have been suggested to be a possible culprit. The present study investigated the association of vitamin D3 treatment on markers of endothelial dysfunction in patients with arterial hypertension. Methods and results: The Styrian Vitamin D Hypertension Trial is a double-blind, placebo-controlled, single-centre study conducted at the Medical University of Graz, Austria. A total of 200 study participants with arterial hypertension and 25(OH)D levels below 30 ng/mL were enrolled. The study participants were randomized to receive 2800 IU of vitamin D3 per day as oily drops (n = 100) or placebo (n = 100) for a duration of eight weeks. The present study uses an analysis of covariance (ANCOVA) to investigate the effect of vitamin D3 treatment on symmetric (SDMA) and asymmetric dimethylarginine (ADMA). A total of 187 participants (mean [SD] age 60.0 [11.3] years; 47% women; 25(OH)D 21.2 [5.6] ng/mL; mean systolic blood pressure of 131.4 [8.9] mmHg on a median of 2 antihypertensive drugs) completed the trial. Mean treatment effect was −0.004 (95%CI [−0.03 to 0.04]; P = 0.819) on ADMA and 0.001 (95%CI [−0.05 to 0.05]; P = 0.850) on SDMA. In the subgroup analysis patients with a 25(OH)D concentration <20 ng/mL had a significant increase in their logl -arginine/ADMA ratio (mean treatment effect 18.4 95%CI [1.84–34.9]μmol/L/μmol/L; P = 0.030). ClinicalTrials.gov Identifier: NCT02136771 EudraCT number: 2009-018125-70 Conclusions: Vitamin D3 supplementation in hypertensive patients with low 25-hydroxyvitamin D has no significant effect on ADMA and SDMA.